2020
DOI: 10.1002/jsfa.10777
|View full text |Cite
|
Sign up to set email alerts
|

Multiple co‐pigments of quercetin and chlorogenic acid blends intensify the color of mulberry anthocyanins: insights from hyperchromicity, kinetics, and molecular modeling investigations

Abstract: BACKGROUND The effect of multiple co‐pigments on the color intensification of mulberry anthocyanins (ACs) using spectroscopic techniques in combination with a molecular docking study was studied. The hyperchromicity of ACs co‐pigmented with chlorogenic acid (CH) and quercetin (Q) blends was measured and their color stability in liquid and encapsulated particle models was evaluated. RESULTS Multiple co‐pigments exhibited higher hyperchromicity, pKH‐values, and heat‐stability than their individual counterparts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…The binding was allowed by increased H-bonding, van der Waals forces, and π-π sites by the extra groups of the multiple co-pigments with AC in aqueous juice and whey particle-based models. Therefore, studies on terpolymer mixtures of phenolic acid-flavonol-anthocyanin are expected to be a promising food colorant ( 107 ). A red pigment can be produced by oxidative coupling of CGA and tryptophan (TRP) in air at pH 9.…”
Section: Application Of Cga In Foodmentioning
confidence: 99%
“…The binding was allowed by increased H-bonding, van der Waals forces, and π-π sites by the extra groups of the multiple co-pigments with AC in aqueous juice and whey particle-based models. Therefore, studies on terpolymer mixtures of phenolic acid-flavonol-anthocyanin are expected to be a promising food colorant ( 107 ). A red pigment can be produced by oxidative coupling of CGA and tryptophan (TRP) in air at pH 9.…”
Section: Application Of Cga In Foodmentioning
confidence: 99%
“…Rosmarinic acid, syringic acid, and catechin showed significant hyperchromic effects for black chokeberry ( Aronia melanocarpa ) anthocyanin [ 291 ]. Molecular modeling results showed that multiple co-pigments may intensify the color of anthocyanins more than individual ligands, and phenolic acid–flavonol–anthocyanin could be used as promising food red-colorants [ 292 ]. Blueberry wines showed higher alcohol and titratable acidity, and lower sugar content by addition of caffeic acid, syringic acid, and quercetin co-pigments during fermentation [ 293 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering three flavan-3-ols (epicatechin, and procyanidin dimers B2 and B2-3′-Ogallate) with a five-fold copigment-to-pigment molar ratio, the measured 𝑝𝐾 ℎ value increased from 2.93 for Mv-glc alone to 3.06, 3.04, and 3.19, respectively, yielding 25, 24, and 31 mol% of red flavylium cation compared to the initial 20 mol% in the absence of flavan-3-ols (González-Manzano et al, 2009). Khalifa et al (2021) found that individual or combined use of chlorogenic acid and quercetin could significantly increase 𝑝𝐾 ℎ values (decrease hydration) of anthocyanin. Both of these cases showed considerable hyperchromic effects of copigmentation due to the alteration of anthocyanin equilibria.…”
Section: Copigmentationmentioning
confidence: 96%
“…Quantitatively, these proportional changes in anthocyanin species could be reflected by the increase in apparent equilibrium constant false(Kafalse)$( {K_a^{\prime}} )$ (Mendoza et al., 2019), or apparent rate constant of hydration ( K ) as expressed by the summation of hydration and proton transfer constants false(K=Kh+Kafalse)$( {K\; = \;{K_h} + {K_a}} )$ (González‐Manzano et al., 2009). K is dominated by Kh${K_h}$ as hydration is predominant over deprotonation at wine pH (i.e., KhKa${K_h} \gg {K_a}$) (González‐Manzano et al., 2009) and sometimes Kh${K_h}$ is solely used regardless of Ka${K_a}$ (Khalifa et al., 2021). Considering three flavan‐3‐ols (epicatechin, and procyanidin dimers B2 and B2‐3′‐O‐gallate) with a five‐fold copigment‐to‐pigment molar ratio, the measured pKh$p{K_h}$ value increased from 2.93 for Mv‐glc alone to 3.06, 3.04, and 3.19, respectively, yielding 25, 24, and 31 mol% of red flavylium cation compared to the initial 20 mol% in the absence of flavan‐3‐ols (González‐Manzano et al., 2009).…”
Section: Reactions Involving Wine Colorationmentioning
confidence: 99%
See 1 more Smart Citation